Developing Digital Books as A Media To Improve Students' Learning Motivation - Yuyun Rahmawati. N; La Ode Fajrul Islam Sabti (Institute Journal and Publication Muhammadiyah University of Buton, 2025)
The development of individuals and societies fundamentally depends on the quality of education provided. Education plays a crucial role in shaping competent, innovative, and responsible citizens who can contribute meaningfully to social progress. However, one of the persistent challenges in the educational process is maintaining students’ motivation to learn. In response to this issue, this research investigates the potential of digital books (e-books) to enhance student motivation. The study explores how e-books, with their multimedia features and interactive capabilities, can offer more engaging and personalized learning experiences. Key advantages of digital books include the ability to incorporate interactive elements such as videos, animations, quizzes, and hyperlinks, which support different learning styles. Additionally, e-books provide students with greater accessibility and flexibility, allowing them to learn anytime and anywhere, thus fostering self-directed learning. The findings of this study highlight that digital book development holds significant promise as a pedagogical tool that not only increases students’ interest but also sustains their motivation to engage with learning materials. In conclusion, integrating digital books into the educational environment can be an effective strategy to support student-centered learning and address the motivational challenges commonly encountered in traditional instructional approaches.